1990
DOI: 10.1007/bf00040264
|View full text |Cite
|
Sign up to set email alerts
|

Digestion of seaweeds by the marine amoeba Trichosphaerium

Abstract: A crude enzyme preparation from the marine amoeba Trichosphaerium was used to produce protoplasts from Sargassum muticum, Macrocystis pyrifera, Porphyra perforata, and other red and brown marcroalgae . Cortical and medullary protoplasts of Sargassum, which were impossible to obtain using mixtures of previously available enzymes, have now been prepared . Intact inner cortical and medullary protoplasts of Macrocystis, which were not observed in past isolations, were obtained . Improved protoplast yields of as mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 7 publications
1
3
1
Order By: Relevance
“…On the other hand, Trichosphaerium maintained in 'axenic' cultures with autoclaved seaweed fragments grew rapidly regardless of the species of algae. In a previous study, Polne-Fuller et al (1990) induced digestive enzyme activity by feeding amoebae on a specific seaweed for one to three weeks, however, in the present study amoebae switched to alternate seaweed diets without noticeable delay in growth or consumption.…”
Section: Seaweed Digestioncontrasting
confidence: 63%
See 3 more Smart Citations
“…On the other hand, Trichosphaerium maintained in 'axenic' cultures with autoclaved seaweed fragments grew rapidly regardless of the species of algae. In a previous study, Polne-Fuller et al (1990) induced digestive enzyme activity by feeding amoebae on a specific seaweed for one to three weeks, however, in the present study amoebae switched to alternate seaweed diets without noticeable delay in growth or consumption.…”
Section: Seaweed Digestioncontrasting
confidence: 63%
“…The present paper draws attention to a protist capable of digesting a wide range of macroalgal carbon and extends earlier work by Polne-Fuller et al (1990) who reported on an algal digesting strain of Trichosphaerium from California. Here, we partially characterize the nature of the digestive enzymes produced by T. sieboldi and present ultrastructural information on the cell wall which gives an insight into how the amoeba may be localizing the activity of extracellular enzymes.…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…Its members are primarily described from marine environments. They are among algae eating protists playing an important ecological role in the marine environment [ 15 , 16 ]. The taxonomy of Trichosphaerium is poorly understood mainly due to the dramatic morphological transformations it undergoes during its life cycle.…”
Section: Introductionmentioning
confidence: 99%